(untitled) (Journal of Parents and Teachers, 2012)
We all take part in the immense puzzle of diversity. If a piece gets lost or doesn’t fit anymore, we will continue trying. Diversity turns out to be richer for all of us. To provoke the participation and the incorporation of all the students is a challenge for the teachers and families. If we think about the students with specific needs derived from motor, sensory and mental characteristics; it is necessary to use our creativity and to search those materials that are adapted to all those differences. The good coordination of the professionals makes possible the progress of students and the great professional satisfaction.